Instilling Honesty through Animated Videos of Prophet Stories in Islamic Religious Education Learning - Cindy Aulia Sari; Hindun Hindun (Journal of General Education and Humanities, 2026)
This study aims to analyze the implementation of animated videos of the Prophet’s stories as a learning medium in Islamic Religious Education (PAI) to foster honesty among seventh-grade students at SMP Negeri 12 Tanjung Jabung Barat. The study is based on the need to strengthen character education through innovative, interactive, and contextual learning media in junior high school settings. A qualitative descriptive approach was employed. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the animated videos were systematically integrated into the introduction, core, and closing stages of the learning process. The learning process encouraged students’ active participation through storytelling, group discussions, reflection activities, and the contextual application of moral values. Students demonstrated a better understanding of honesty and responded positively to animated videos, indicating greater engagement and interest during classroom activities. The learning activities also provided students with opportunities to reflect on and apply honesty in their daily lives. Overall, the findings indicate that animated videos of the Prophet’s stories can support students’ engagement and the gradual internalization of values of honesty while enriching the learning experience in Islamic Religious Education. These findings highlight the potential of animated storytelling as a meaningful medium for integrating character education into classroom practice.